INCENTIVES TO THE IMPLEMENTATION OF QUALITY OF AGRICULTURAL AND FOOD PRODUCTS IN SERBIA - Edin Kalač (Ekonomika Poljoprivrede (1979))
Since agricultural products and food industry are among our countrys major trumps, it is essential for the enterprises from this sector to realize in time the importance of safety and quality food management standards and start their implementation process. Effects that are achieved after standard implementation has a purpose in faster integration process of Serbia and EU. The paper deals with modern business trends in food production. Further is described situation in the food industry of Serbia in the period of transition and necessity of introduction standards for quality management systems in the enterprises, The paper further describes financial support by the Ministry of Agriculture of the Republic of Serbia and international donors in the period 2004- 2010. and impact of implementing standards for exporting agricultural and food products from Serbia.